Russia, the European Union and NATO Is a "new normal" possible? - Staack, Michael (WIFIS-aktuell, 2018)
Russia, the European Union, and NATO still share some important common interests that need to be given greater attention. A return to strategic partnership is not conceivable without resolving the Ukraine confl ict, but prudent management of the antagonism in order to keep open the prospect of a peaceful new normal is crucial. At the same time, it is important to keep in mind that the persistent volatility of the international environment could further complicate this already diffi cult process.